2016
DOI: 10.1080/21655979.2016.1200772
|View full text |Cite
|
Sign up to set email alerts
|

Is the LysM domain ofL. monocytogenesp60 protein suitable for engineering a protein with high peptidoglycan binding affinity?

Abstract: Lysin motif (LysM) is a highly conserved carbohydrate binding module that is widely present in proteins from both prokaryotes and eukaryotes. LysM domains from many LysM-containing proteins can be taken out of their natural context and retain their ability to bind peptidoglycan. Therefore, LysM has enormous potential for applications in both industry and medicine. This potential has stimulated an intensive search for LysM modules with different evolutionary origins. The p60 protein (Lm-p60) is an NlpC/P60-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…These two latter enzyme families contain a circularly permuted catalytic domain where the relative positions of the cysteine and histidine/polar residue of the conserved catalytic triad are swapped in the primary sequence (Anantharaman and Aravind, 2003). In B. subtilis , LytF and LytE, which belong to the P60-like family, break the linkage of m-diaminopimelic acid of the PG (Yu et al, 2016). Structure determination of NlpC/P60 domain in CwlT from Clostridioides difficile , previously known as Clostridium difficile or Peptoclostridium difficile (Yutin and Galperin, 2013; Lawson et al, 2016), revealed a conserved Cys-His-His-Tyr active site specific to tetrapeptide (Xu et al, 2014).…”
Section: Cell Wall Hydrolases In Bacteriamentioning
confidence: 99%
“…These two latter enzyme families contain a circularly permuted catalytic domain where the relative positions of the cysteine and histidine/polar residue of the conserved catalytic triad are swapped in the primary sequence (Anantharaman and Aravind, 2003). In B. subtilis , LytF and LytE, which belong to the P60-like family, break the linkage of m-diaminopimelic acid of the PG (Yu et al, 2016). Structure determination of NlpC/P60 domain in CwlT from Clostridioides difficile , previously known as Clostridium difficile or Peptoclostridium difficile (Yutin and Galperin, 2013; Lawson et al, 2016), revealed a conserved Cys-His-His-Tyr active site specific to tetrapeptide (Xu et al, 2014).…”
Section: Cell Wall Hydrolases In Bacteriamentioning
confidence: 99%
“…The30kDa urease subunit alpha (ureA) from Helicobacter pylori acts as virulence factor and cause infection in stomach via host-pathogen interaction ( Schoep et al, 2010 ) and mediate immune response in humans ( Schoep et al, 2010 ). The endopeptidase p60 (Lm-p60) of Listeria monocytogenes whose sequence was also predicted in similar search is a highly conserved carbohydrate binding module which can be engineered for binding to peptidoglycans with high affinity ( Yu et al, 2016 ). Mycobacterium leprae has two proteins (ESAT-6 like protein esxb and 10 kDa chaperonin groS) that showed molecular similarity with predicted antigens in SARS-CoV-2 RBD.…”
Section: Resultsmentioning
confidence: 99%
“…The peptidoglycan endopeptidase LytE breaks the linkage of m -diaminopimelic acid of the peptidoglycan ( 66 ), and putative homologs are present in marine Prochlorococcus and Synechococcus (tables S3 to S5). In contrast, YmdB protein, which was shown to be important for nanotube formation in B. subtilis ( 8 ), was not found in picocyanobacteria.…”
Section: Methodsmentioning
confidence: 99%